Relative age effects in political selection - Janne Tukiainen; Tuomas Takalo; Topi Hulkkonen (Bank of Finland, 2018)
We exploit a regression discontinuity design to provide causal evidence of the relative age effect (RAE) on a long-run adult age outcome: Political selection. We find strong evidence of the RAE in politics in Finland. However, the effect is heterogeneous: We find that male candidates born early in the calendar year have a significantly higher probability of getting elected to the parliament but no similar RAE applies to female candidates nor to municipal elections. Moreover, this effect only takes place in the most competitive parliamentary districts and is present only for some parties. We also find that in all the groups where the RAE does not exist, early-born candidates are under-represented suggesting attrition of talent in the candidate placement. Overall, our results show that seemingly artificial cutoffs imposed by the government have persistent consequences even on the selection to the highest positions of power within a society.
URN:NBN:fi:bof-201808081924
Keywords: C21; D72; J13; J16; J24; 330